Positive Learning Environment and Mistreatment Prevention Module - Judith Lewis; Nathalie Feldman; Anne Rich; Sean Ackerman; Charmaine Patel (Association of American Medical Colleges, 2015)
Abstract This multimedia module is designed to increase awareness of and knowledge about the national problem of medical student mistreatment as defined by the Association of American Medical Colleges for all participants in the learning environment. The modules also provide an opportunity to (1) communicate institutional efforts to prevent and eliminate mistreatment in the learning environment; (2) post institutional policies and reporting routes for mistreatment; and (3) collect documentation that learners have thoroughly reviewed this material and are aware of institutional policies via an attestation prompt and postmodule quiz. So far, we have assigned a pilot version of the module to medical students at two curriculum points, in the second year prior to the start of the clerkships and in the fourth year prior to graduation. These assignments have used the attestation function to demonstrate student awareness of the policy and procedures regarding student mistreatment. One pitfall of the original version of the module is its length, especially when used in conjunction with classroom discussion. For this purpose, we created a shortened version of the module without the film for assignment prior to conducting a film and discussion session. We plan to use this during orientation for incoming clerkship students and new residents. The module has been well received by students, residents, faculty, and staff at our institution and by colleagues at other institutions who saw earlier versions. Viewers appreciate that the module captures the nuances and ambiguity inherent in the problem of mistreatment rather than simplifying the issue by using black-and-white examples.